Functional analysis of a WRKY transcription factor involved in transcriptional activation of the DBAT gene in Taxus chinensis. (12th June 2012) - Li, S.; Zhang, P.; Zhang, M.; Fu, C.; Yu, L.
Abstract Although the regulation of taxol biosynthesis at the transcriptional level remains unclear, 10‐deacetylbaccatin III‐10 β‐O‐acetyl transferase (DBAT) is a critical enzyme in the biosynthesis of taxol. The 1740 bp fragment 5′‐flanking sequence of the dbat gene was cloned from Taxus chinensis cells. Important regulatory elements needed for activity of the dbat promoter were located by deletion analyses in T. chinensis cells. A novel WRKY transcription factor, TcWRKY1, was isolated with the yeast one‐hybrid system from a T. chinensis cell cDNA library using the important regulatory elements as bait. The gene expression of TcWRKY1 in T. chinensis suspension cells was specifically induced by methyl jasmonate (MeJA). Biochemical analysis indicated that TcWRKY1 protein specifically interacts with the two W‐box (TGAC) cis‐elements among the important regulatory elements. Overexpression of TcWRKY1 enhanced dbat expression in T. chinensis suspension cells, and RNA interference (RNAi) reduced the level of transcripts of dbat. These results suggest that TcWRKY1 participates in regulation of taxol biosynthesis in T. chinensis cells, and that dbat is a target gene of this transcription factor. This research also provides a potential candidate gene for engineering increased taxol accumulation in Taxus cell cultures.